GAGASAN IDEALISASI PEMBELAJARAN BIOLOGI DARI BERBAGAI SUDUT PANDANG - Andi Basliahwanti Murti; Abdul Rasyid Fakhrun Gani; Devi Alvionita (Bioilmi: Jurnal Pendidikan, 2021)
Education is a very important learning process for the nation's children, because with an advanced education it symbolizes an immediate progress as well. In connection with this, it is known that there is a philosophical basis for idealism, realism, pragmatism, and others. The idealization of Indonesian education can be seen from various points of view, namely teachers, students and the government. Teachers are real changers in society. Therefore, teachers are involved effectively, both as educators and social activists. Students are one of the main subjects in the education system. While the government is a facilitator for education in this country. The government must be wise in setting a rule, not to mention the issue of education, the government as a leader has the authority to formulate a strong policy to formulate education policy